Settlement and Capacity Analysis of Land Support Development on Flyover in Large City; Pekanbaru, Indonesia - Husnul Kausarian; evan trionaldi; taufan Khalif Arrahman; dewandra bagus eka putra; Batara (UIR PRESS, 2020)
The study area located on the street of Soebrantas to Soekarno Hatta Street, with the coordinate position of 0 ° 30 ' 0.79